Damage behavior analysis of unidirectional fiber reinforced shape memory polymer composites. (15th January 2023) - Liu, Zhengxian; Mu, Tong; Lan, Xin; Liu, Liwu; Bian, Wenfeng; Liu, Yanju; Leng, Jinsong
Highlights: The stress state and damage modes of SMPC were analyzed theoretically. Considering the compressive strain of matrix, the strain energy of matrix cracking and fiber fracture damage systems were developed. The neutral surface position, critical buckling position, critical damage position, and half-wavelength were solved by using the minimum energy principle. The expressions and evolution rules during the damage propagation process were obtained by energy method. Abstract: Shape memory polymer composites (SMPCs) are gradually being used in space deployable structures due to their unique shape memory properties and variable stiffness characteristics. Currently, the damage behavior of SMPC has not been systematically investigated, which affects its structural design and application. In this study, the damage behavior analysis of unidirectional fiber-reinforced SMPCs was investigated. The buckling deformation and damage modes of SMPC were analyzed theoretically. The strain energy of the matrix cracking and fiber fracture damage system was developed considering the compressive strain of the matrix. Additionally, the analytical expressions of the key parameters during bending were determined and the law of evolution was revealed. The damage mode analysis showed that decreasing fiber volume content and increasing thickness were more likely to result in matrix cracking damage. The fiber fracture would occur in the stretching region if the fiber volume content was less than a certain value. Finally, the experiment was performed to demonstrate the validity of the theoretical method. This work is significant for the design and optimization of the SMPC-based structure.